Efeito da Seleção para Peso Pós-desmama sobre Indicadores da Eficiência Produtiva de Vacas da Raça Nelore - De Vasconcelos Silva, Josineudson Augusto I.I. [UNESP]; Razook, Alexander George; Tonhati, Humberto [UNESP]; De Figueiredo, Leopoldo Andrade (My University, 2000)
The objective of this study was to evaluate the productivity efficiency indicators of cows selected for post-weaning weight, with emphasis in the calf-cow weight ratios, in a controlled herd (NeC), unselected for post-weaning weight, selection (NeS) and conventional (NeT). The analysis involved 3929 and 3906 calves weights at the 120 (P120) and 210 (P210) days of age, respectively. The cow weights at those ages were also considered, and the recorded numbers were 3824 (PV120) and 3777 (PV210), respectively, for 120 and 210 days. The analysis included 183, 375 and 554 cows from NeC, NeS and NeT, respectively. The SAS/ GLM procedure was used in the data analyses. The model included the effects of herd, year and month of birth, and sex of calf, age of cow at calving, and the interactions herd x year, and year x month of birth. All effects were significant. The results showed a positive correlated response in the selection for post weaning on the calf weights and, low response, on cow weights. The calf weight/cow weight ratios showed average adjusted values of 249.0±2.1, 253.7±1.6 and 255.8±1.2 g/kg for R120, and 362.9±2.8, 368.5±2.1 and 374.6±1.7 g/kg for NeC, NeS and NeT at R210 respectively, and indicated that, at both ages, the NeS and NeT herds produced more kg of calf by kg of cow when compared to NeC.
Effects of Selection for Post Weaning Weight on Nellore Cow Productivity Efficiency Indicators
Keywords: Coes; Maternal hability; Nellore; Post-weaning weight; Selection